A review on working and applications of oxy-acetylene gas welding. (2021) - Singh, Rudra Pratap; Kumar, Subodh; Dubey, Somil; Singh, Aman
Abstract: Oxy-acetylene welding and cutting processes are popular, easily available and one of the cheapest methods of working with metals. Welding process is used by many construction and manufacturing firms. There are several welding processes to join materials to achieve the desired purpose. Gas welding is one of the cheapest processes of welding and generally used in all the small scale works. The oxygen and the acetylene are the two gasses which produce sufficient heat and temperature which can be utilized for joining the materials. It is widely used for welding pipes and tubes and also for repair work in industries. The main object of industries is to produce better quality product at minimum cost. The joints made by gas welding should be strong enough to bear the loads applied on it. The joints fail due to several different reasons. The failure of the joints is a complicated problem and the researchers are working for the construction of optimum weld. Cutting of metals and alloys is also required in many industries which can easily be done with oxy-acetylene gas welding. In this work several important research papers on oxy acetylene gas welding were selected for analysis and investigation. The work and concept of each researcher is expressed in such a way that the future scope should be clear. The researchers have given their own views on the performance of the gas welding process, the materials selected for their study, effect of ratio of oxygen to acetylene etc. in their researches. In this research review work different other research papers which contained the research and analysis relating input and output parameters of welding and cutting, flames, nozzle design, effects of pre and post heat treatments and snapping were included and considered while working with oxy acetylene gas welding.